Biodynamic farming as a resource for sustainability transformations: Potential and challenges. (June 2022) - Rigolot, C.; Quantin, M.
Abstract: Biodynamic farming is increasingly popular among farmers and consumers, but it is still dismissed as pseudoscience by part of the scientific community. In this article, we first present an overview of biodynamic farming, its current development, foundations and three specific principles: 1) the farm seen as a living organism; 2) Preparations; 3) Cosmic rhythms. Then, we show that pragmatic scientific approaches are compatible with biodynamic farming, and suggest an interesting potential for sustainability. Particularly, anthropological studies demonstrate that beliefs and spirituality in biodynamic farming contribute to a unique relationship of care between farmers and nature. Contrary to a common misconception, biodynamic farmers are shown to be open to scientific knowledge, which they manage to combine creatively with experiential and spiritual knowledge. At farm scale, although still rare, holistic multicriteria assessment studies suggest fairly satisfactory overall sustainability performances. Biodynamic farming has also already proven to be useful in transdisciplinary action-research projects with diverse stakeholders, to produce original "actionable knowledge" for sustainability. Overall, we conclude that biodynamic farming can be a valuable resource for "reenchanting" agriculture, in a comparable and complementary way to indigenous knowledge. However, it must not be seen as a panacea, and its organization and the major role of beliefs especially raise legitimate concerns. More research is needed to better understand the specific advantages and difficulties of biodynamic farming. Three key research perspectives are identified: 1) Farmers' decision-making; 2) Farming system design and evaluation; 3) Transformation pathways. Graphical abstract: Unlabelled Image Highlights: Biodynamic farming relies on a specific conception of knowledge, based on farmers' creativity, intuition and experience Biodynamic farming is compatible with holistic and pragmatic research approaches aiming for "actionable knowledge" The spirituality, beliefs and mystery surrounding biodynamic practices facilitate unique relationships of care between human beings and nature Academic research could benefit from studying biodynamic farming more, and biodynamic farming could benefit more from academic research Key challenges are the study of innovation processes and transformation pathways, improved dialogue, evaluation and funding